SHEPWM control technology of real coding genetic simulated annealing algorithm - Ye, Man-yuan; Huang, Kai-feng; Song, Ping-gang; Li, Song (Dianji yu Kongzhi Xuebao = Electric Machines and Control, 2017)
In view of solving the SHEPWM harmonic elimination model,a hybrid algorithm was proposed,which was composed of genetic algorithm and simulated annealing algorithm. According to the value of individual fitness,the adaptive crossover and mutation were performed,and the simulated annealing algorithm was adopted to improve the individual update,thus the diversity of group was increased. The ability of global optimization was enhanced and the local optimum was avoided,using real coding to save the individual to improve calculation accuracy. Taking the SHEPWM in neutral pointed clamped three level inverter as an example,the trajectory of switching angles under the whole modulations and another two sets of feasible solution under high modulations were given,and a curve for the THD varies modulation was drawn. Simulation and experiment results certificate the angles worked out by the proposed algorithm is correct and valid.